Cathedral Cities of Spain: 60 Reproductions from Original Water Colours - Collins, W. W. (William Wiehe), 1862-1951 (Salt Lake City, UT : Project Gutenberg, 2010)
"Cathedral Cities of Spain: 60 Reproductions from Original Water Colours by Collins" is an illustrated collection created by William Wiehe Collins. Likely written in the early 20th century, this book presents a compilation of exquisite watercolour reproductions of various Spanish cathedrals. It captures a rich visual historical account of these architectural landmarks, aiming to highlight their beauty and significance. The book features 60 beautiful reproductions that showcase renowned Spanish cathedrals such as those found in Barcelona, Toledo, and Santiago. Each illustration offers a glimpse into the intricate details and grandeur of the structures, serving both as an artistic celebration and a valuable resource for those interested in architecture and art. Accompanying titles hint at the featured sites, inviting viewers to immerse themselves in the diverse cultural heritage and architectural marvels of Spain. Overall, it serves as a visual feast for art lovers, architecture enthusiasts, and anyone with an appreciation for the historical richness of Spain's cathedral cities. (This is an automatically generated summary.)
Release date is 2010-05-05
E-text prepared by Chuck Greif from page images generously made available by Internet Archive (http://www.archive.org)
Keywords: Spain -- Description and travel; Cathedrals -- Spain